Impact of Armed Conflicts on Education and Educational Agents: A Multivocal Review - Cervantes-Duarte, Luisa (2016)
This paper investigates the short and long-term pernicious impact of armed conflicts on education and educational agents (students, teachers and students’ parents), using a multivocal review by means of the integration and qualitative analysis of 60 research reports (voices) found in two databases: Web of Science and PROQUEST in the period between 1995 –date of the first founding paper- until 2014. Through the analysis of source data (voices) and taking the “multivocal review” as a method, the voices have been combined in nine categories, namely: a) Refusal and impediments to a return to education; b) Educational infrastructure damaged or destroyed; c) Cuts in or withdrawal of spending on education; d) Loss of the educational and protective functions of the family; e) Loss of the academic community; f) Non-qualified teaching staff; g) Drastic loss of skills; h) Abandoning school (population movements, destruction of networks and social environment); i) Behavioural problems: traumas, pedagogical roles and self-victimization. These categories have highlighted the serious consequences arising from conflicts, infringing as they do the most basic human rights and in particular the right to a sound education during childhood.